Effect of substrata on the development of stem cuttings of Lippia alba (Mill.) N. E. BR. - Limonene-carvone chemotype - Ehlert, P. A D [UNESP]; Chaves, F. C M [UNESP]; Ming, L. C. [UNESP]; Da Silva, M. A S [UNESP] (My University, 2002)
Studies were conducted to show the effect of different substrata on the development of stem cuttings of Lippia alba made of limonene-carvone chemotype. The experiment was done in the College of Agronomical Sciences, UNESP, Botucatu, SP, Brazil in 2000. The cuttings were planted in polystyrene trays consisting of 72 cells. The cuttings had about 0.20 m of length and were put in the following substrata: Fine sand (T1), commercial substratum (T2), carbonised rice peel and local soil (T3), local soil, cow manure and carbonised rice peel (T4), vermiculite (T5), and carbonised rice peel (T6). After 40 days the development of stem cuttings were evaluated. High rate of rooting of stem cuttings was verified, with average of 95% and no significant difference between the treatments. In relation to dry mass of aerial parts and dry mass of roots, significant differences were found. For dry mass production of aerial parts the commercial substratum (T2) and the local soil, cow manure, carbonised rice peel (T4) were optimal. For mass of roots the local soil, cow manure, carbonised rice peel (T4) proved to be the best.
Keywords: cidreira; Carbonised rice peel substratum; Cow manure; Dry mass of aerial parts; Dry mass of roots; Rooting; Stem cuttings